2021
DOI: 10.26434/chemrxiv-2021-dctkq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The NIH Lipo-COVID Study: A pilot NMR investigation of lipoprotein subfractions and other metabolites in patients with severe COVID-19.

Abstract: A complex interplay exists between plasma lipoproteins and inflammation, as evidenced from studies on atherosclerosis. Alterations in plasma lipoprotein levels in the context of infectious diseases, particularly respiratory viral infections, such as SARS-CoV-2, have become of great interest in recent years, due to their potential utility as prognostic markers. Patients with severe COVID-19 have been reported to have low levels of total cholesterol, HDL-cholesterol, and LDL-cholesterol, but elevated levels of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 49 publications
(58 reference statements)
0
8
0
Order By: Relevance
“…Our current study further extends previous findings by demonstrating a substantial reduction in the proportion of large HDL 2a subclasses, with a concomitant increase of the smallest HDL 3c particles during the hospitalisation of patients with severe disease. It should be stressed that Ballout et al [24] reported that a third of patients with severe COVID-19 had reduced concentrations of small-sized LDL particles. Similarly, in our current study, the patients with moderate rather than severe COVID-19 had the highest proportion of small LDL III particles.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our current study further extends previous findings by demonstrating a substantial reduction in the proportion of large HDL 2a subclasses, with a concomitant increase of the smallest HDL 3c particles during the hospitalisation of patients with severe disease. It should be stressed that Ballout et al [24] reported that a third of patients with severe COVID-19 had reduced concentrations of small-sized LDL particles. Similarly, in our current study, the patients with moderate rather than severe COVID-19 had the highest proportion of small LDL III particles.…”
Section: Discussionmentioning
confidence: 98%
“…So far, data on HDL particles distribution in COVID-19 has remained scarce. A small pilot study by Ballout et al [24] was the first that investigated NMR-based lipoprotein subclasses profile in severe COVID-19 patients. The authors found a significant reduction of HDL particles number, especially small HDLs, on hospital admission.…”
Section: Discussionmentioning
confidence: 99%
“…It is also known that LDL and cholesterol are key mediators of inflammation ( Chróinín et al, 2014 ), which could also have a different extent in recovered and naïve subjects following vaccination. Notably during acute COVID-19 infection, where both lipid bilayer degradation induced by the spike protein and severe inflammation occur, cholesterol and LDL5 are also significantly altered with respect to healthy values, Figure 4 , first column ( Bruzzone et al, 2020 ; Kimhofer et al, 2020 ; Ballout et al, 2021 ; Bizkarguenaga et al, 2021 ; Lodge et al, 2021 ; Masuda et al, 2021 ; Meoni et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…1 H nuclear magnetic resonance (NMR) spectroscopy analysis of biofluids produces profiles that show characteristic responses to changes in physiological status and has been used in a few studies in the past to monitor changes in urinary metabolite levels in mice administered different types of influenza vaccines ( Sasaki et al, 2019 ) or to identify serum markers predictive of adverse reactions against smallpox ( McClenathan et al, 2017 ) as well as metabolic signatures of responses induced by a series of commonly used human vaccines, as reviewed in ( Diray-Arce et al, 2020 ). On the other hand, 1 H NMR has been also successfully used to monitor changes in metabolites and lipoproteins induced by SARS-CoV-2 infection ( Bruzzone et al, 2020 ; Kimhofer et al, 2020 ; Ballout et al, 2021 ; Baranovicova et al, 2021 ; Bizkarguenaga et al, 2021 ; Julkunen et al, 2021 ; Lodge et al, 2021 ; Masuda et al, 2021 ; Meoni et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, no prior reports have described significant LpX accumulation in patients with post-COVID-19 cholangiopathy. Interestingly, a pilot study assessing lipoprotein subfractions by nuclear magnetic resonance in patients with severe COVID-19, but without cholangiopathy, found that 70% of these patients had detectable levels of LpX ( 8 ). So, it is possible that severe COVID-19 may contribute to LpX accumulation independently of liver function.…”
Section: Introductionmentioning
confidence: 99%